Sekolah unggul tak lahir dari kurikulum hebat, tapi dari manajemen yang efektif - Nafia, Jilan (Maliki Interdisciplinary Journal, 2025)
An excellent school is not created merely by having an outstanding curriculum, but through the implementation of effective educational management that focuses on the quality of education itself. The curriculum serves only as a tool to achieve educational goals, while management functions as the driving force that ensures all school members work together harmoniously. Effective educational management includes well directed and continuous planning, organizing, implementation, and supervision. Schools with strong management are able to build visionary leadership, professional teachers, and a collaborative as well as disciplined work culture. Conversely, without effective management, the curriculum often remains merely an administrative document with no real meaning in classroom practice. Therefore, the key to realizing an excellent school does not lie in how often the curriculum changes, but in how the management system is able to manage human resources, facilities, and learning strategies professionally and measurably to achieve sustainable educational quality.